Consumer Attitude Towards Green Marketing - A Study at Sirsa District (Haryana) - Bansal, Monica (Gyan Management Journal, 2012)
Times are tough for marketers of branded products. Brand loyalty is near all-time low, and percentage of people who feel that some brands are worth paying more for is declining. In such tough competitive climate, environmentally, compatible companies would only survive. Today consumers are even more conscious than ever, as they prefer to purchase those products and packages that can be recycled or ifely be disposed of Today’s consumer prefers eco- labeled products that are not only environmentally endly but also ecologically safe. The reasons for such behavioural change among consumers are ;erouse they foresee things to get worse as no place of the globe will escape the by-products of echnologica/ Innovations, rapid industrialization and population growth. In fact industrial activities the past half century have created serious ecological problem like global warming, Ozone depletion, of bio-diversity, natural resource scarcity, air pollution, acid rain, taxic wastes and industrial accidents.